Equilibrium in women with osteoporosis submitted to balance training with and without an oscillating vibratory pole - Ruzene, Juliana Rodrigues Soares [UNESP]; Morcelli, Mary Hellen [UNESP]; Navega, Marcelo Tavella [UNESP] (Elsevier, 2016)
Objectives: An eight-week balance training program, with and without oscillation of vibratory pole, was shown to have a medium-term persistence effect on the performance of elderly physically-active women with osteoporosis. Methods: The 29 women who completed the study were randomly separated into two groups: an Oscillating Pole Group (OPG; 69.6 ± 5.8 years; n = 14) and a Non-Oscillating Pole Group (NPG; 70.9 ± 7.4 years; n = 15). The improvement in equilibrium was evaluated using the Berg Balance Scale before training, after training and in the Follow-Up (eight-weeks after the conclusion of the training). Results and discussion: The NPG presented both Post-Training (=018 relative to pre-training) and Follow-Up (=007) improvements in equilibrium. The improvement for OPG was near significant (=051 relative to pre-training) in Post-Training and significant (=038) in the Follow-Up. There were no significant differences between Post-Training and Post-Follow-Up (=999) for either group or in the intergroup comparisons (no statistically-significant effect of oscillation of the pole).
Keywords: Elderly; Fall accidents; Postural balance